The Costs of Macroprudential Deleveraging in a Liquidity Trap - Chen, Jiaqian (IMF Working Papers; Working Paper, 2020)
We examine the effects of various borrower-based macroprudential tools in a New Keynesian environment where both real and nominal interest rates are low. Our model features long-term debt, housing transaction costs and a zero-lower bound constraint on policy rates. We find that the long-term costs, in terms of forgone consumption, of all the macroprudential tools we consider are moderate. Even so, the short-term costs differ dramatically between alternative tools. Specifically, a loan-to-value tightening is more than twice as contractionary compared to loan-to-income tightening when debt is high and monetary policy cannot accommodate.